The Holy Spirit and Christian origins: essays in honor of James D. G. Dunn - Stanton, Graham; Dunn, James D. G.; Longenecker, Bruce W.; Barton, Stephen C. (Eerdmans, 2004)
Anyone who is interested in the rigorous study of early Christianity and who has not engaged with the works of James D. G. Dunn is not really interested in the rigorous study of early Christianity. No one would dispute that Professor Dunn is one of the most prolific New Testament scholars of the late twentieth and early twenty-first centuries. And while a handful of scholars might have a list of publications to rival his own extensive publications list, none of them could claim to have set the agenda of scholarly study to the extent that Jimmy Dunn has done for a sustained period of time since the 1970s.The Holy Spirit and Christian Origins comprises a selection of original essays that explore a topic that has held a prominent and distinctive place in the majority of Professor Dunn's publications. Written by twenty-seven leading scholars, this singular volume probes deep into the nascent Christian communities and their writings and investigates the early Christians' convictions concerning the Holy Spirit. Ranging widely through Scripture and across early church history, many of these essays introduce groundbreaking research in biblical studies, and some engage directly with Dunn's work in the field.Presenting some of the best new work in New Testament studies as well as celebrating a respected career, The Holy Spirit and Christian Origins will help to stimulate further discussion and reflection in the theological academy and in the Christian church - two sectors that Jimmy Dunn has consistently and passionately sought to straddle, nurture, and refresh.